Representation of Age Gap in The Film ‘Sweet 20’ - Agustini Sinaga; Debora Siregar; May Syaroh; Safjinatul Hasanah Harahap4 (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research examines the representation of the age gap in the film ‘Sweet 20’ using a qualitative descriptive approach. The film focuses on the theme of ageism seen in the interaction between the older and younger generations ranging from family environment, peers, public places, to the desire to be young again. This research found that the film ‘Sweet 20’ displays significant ageism, especially in how the older generation is considered unproductive and does not have a significant role in the family. The results of this study show that the film ‘Sweet 20’ represents ageism as a common culture in society, where the older generation is considered to have no value and no significant role in family life. This study also found that the film ‘Sweet 20’ not only presents ageism as a culture, but also as part of a social structure that affects the behaviour of individuals in society. Thus, this research shows that the film ‘Sweet 20’ has significant power in understanding and critiquing ageism as a common culture in society.